Development and Application of a Novel Rapid and Throughput Method for Broad-Spectrum Anti-Foodborne Norovirus Antibody Testing - Zuo, Yueting; Xue, Liang; Gao, Junshan; Liao, Yingyin; Jiang, Yueting; Li, Ying; Liang, Yanhui; Wang, Linping; Cai, Weicheng; Cheng, Tong; Wang, Juan; Chen, Moutong; et al. (Frontiers in Microbiology, 2021)
Foodbone norovirus (NoV) is the leading cause of acute gastroenteritis worldwide. Candidate vaccines are being developed, however, no licensed vaccines are currently available for managing NoV infections. Screening for stimulated antibodies with broad-spectrum binding activities can be performed for the development of NoV polyvalent vaccines. In this study, we aimed to develop an indirect enzyme-linked immunosorbent assay (ELISA) for testing the broad spectrum of anti-NoV antibodies. Capsid P proteins from 28 representative NoV strains (GI.1-GI.9 and GII.1-GII.22 except GII.11, GII.18, and GII.19) were selected, prepared, and used as coating antigens on one microplate. Combined with incubation and the horseradish peroxidase chromogenic reaction, the entire process for testing the spectrum of unknown antibodies required 2 h for completion. The intra-assay and inter-assay coefficients of variation were less than 10%. The new method was successfully performed with monoclonal antibodies and polyclonal antibodies induced by multiple antigens. In conclusion, the indirect ELISA assay developed in this study had a good performance of reliability, convenience, and high-throughput screening for broad-spectrum antibodies.